Effects of serum, enzyme, thiol, and forced degradation on the stabilities of αO‐Conotoxin GeXIVA[1, 2] and GeXIVA [1, 4]. (30th January 2018) - Yu, Shurun; Wu, Yong; Xu, Pan; Wang, Shuai; Zhangsun, Dongting; Luo, Sulan
Abstract : αO‐conotoxin GeXIVA, which is a potent antagonist of α9α10 nicotinic acetylcholine receptor (nAChR), is of great interest as a potential analgesic for chronic neuropathic pain. It has three isomers, of which both GeXIVA[1, 2] and GeXIVA[1, 4] showed similar low nanomolar IC50 s in potent blocking rat α9α10 nAChRs. Here, we first reported stabilities of GeXIVA[1, 2] and GeXIVA[1, 4] in various biochemical circumstances, including human serum, enzymatic degradation, and thiol, which would be the key factors to affect stabilities of the two isomers in vivo. Simultaneously, forced degradation was carried out to evaluate stabilities of the two isomers. GeXIVA[1, 2] and GeXIVA[1, 4] were unstable when they were incubated in serum and digestive enzymes at 37°C. Their disulfide bond frameworks were easy to be scrambled in GSH and HSA. For different stress conditions, their stabilities were impacted greatly by oxidation, temperature, and alkaline conditions. The results may provide a foundation for storage conditions, structural modification, and pharmaceutical preparation of GeXIVA[1, 2] and GeXIVA[1, 4]. Abstract : αO‐conotoxin GeXIVA is of great interest as a potential analgesic for chronic neuropathic pain. The stabilities of GeXIVA were evaluated at the first time, which may provide a foundation for storage conditions, structural modification, and pharmaceutical preparation of GeXIVA.